Pattern and predictors of complementary and alternative medicine (CAM) use among pediatric patients with epilepsy - Driedger, Jan Henje; Reuner, Gitta; Kadish, Navah; Pietz, Joachim; Schubert-Bast, Susanne (Epilepsy & behavior, 2013)
Parents of pediatric patients with chronic conditions such as epilepsy increasingly opt for complementary and alternative medicine (CAM). However, data on the pattern and reasons of CAM use in childhood epilepsy are scarce. The objectives of this study were as follows: first, to characterize CAM use among pediatric patients with epilepsy by assessing its spectrum, prevalence, costs, and frequency of use; second, to evaluate the influence of CAM use on compliance and satisfaction with conventional care as well as to explore parent-child neurologist communication concerning CAM; and third, to investigate predictors of CAM use. A postal survey was administered to all parents of pediatric outpatients with epilepsy aged 6 to 12, who have received treatment at the neuropediatric outpatient clinic of the University Children's Hospital Heidelberg between 2007 and 2009. One hundred thirty-two of the 297 distributed questionnaires were suitable for inclusion in statistical analysis (44.7%). Forty-nine participants indicated that their children used CAM during the previous year (37.1%). Thirty different types of CAM were used, with homeopathy (55.1%), osteopathy (24.5%), and kinesiology (16.3%) being the most commonly named. A mean of 86€ (0€-500€) and 3h (1 h-30 h) per month was committed to CAM treatment. Only 53% of the users informed their child neurologist of the additional CAM treatment, while 85.6% of all parents wished to discuss CAM options with their child neurologist. Seventy-five percent of users considered the CAM treatment effective. Among the participants most likely to seek CAM treatment are parents whose children show a long duration of epileptic symptoms, parents who make use of CAM treatment themselves, and parents who value a holistic and natural treatment approach. A substantial portion of pediatric patients with epilepsy receive CAM treatment. The high prevalence of use and significant level of financial and time resources spent on CAM indicate the high importance of these treatment options for parents. On the other hand, communication concerning CAM with the child neurologist is largely insufficient despite the wish to speak about CAM. Complementary and alternative medicine users' high compliance with conventional treatment and high perceived effectiveness of CAM support an integrative approach to CAM for pediatric patients with epilepsy. Our study implies that in addition to open parent-child neurologist communication, active inquiry on CAM treatments is necessary to enable informed decision making by parents and to establish the suitability of CAM treatment for the patient. Reliable predictors for CAM use, which allow for improved identification of patients with a high likelihood to receive CAM treatment, are the duration of the illness, use of CAM by the parents themselves, and the desire of the parents to receive a holistic and natural treatment for their child.